Immobilization of Vibrio cholerae S1 (NAG) L-Glutaminase on Different Supports - Shatha Salman Hassan (مجلة بغداد للعلوم, 2010)
Sixteen Vibrio isolates producing L-glutaminase were obtained from clinical and water samples , one isolate was selected according to its’ highest enzyme productivity , it was identified as Vibrio cholerae (NAG) and coded as V. cholerae S1.